Peran Keluarga dan Pengaruhnya dalam Membentuk Perilaku Moral Remaja di Kelurahan Sindang Rasa Bogor Timur - Susanti Mulyanengsih; Hartin Kurniawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
The purpose of this study is to find out how the role of family affect the moral behavior of adolescent in RW 10 Sindang Rasa East Bogor.The family background is based on family interests as the first place where adolescent moral value are formed. Using quantitative research with an associative approach. This study involved 113 adolescents between the age of 13-18 years, 53 respondents were selected by purposive sampling technique with the slovin formula (e=10% ), after the data were collected using a likert scale questionnaire tested using validity. Reliability, normality, and linearity tests as, well as sample linear regression analysis with SPSS. The results show that the role of the family has a positive and significant effect on how adolescents behave morally, the value of the correlation coefficient is strong and the value of the significant of alfha shows this fact. Thus, the better the role of the family is providing nurturing, guidance and supervision, the better the moral behavior of adolescentsin their environment Therefore, the role of the family plays a very important role in shaping and optimizing adolescents moral behavior. It is hoped that is research will provide useful information for families and related paties to. help the development of adolescents as positively as possible.